A thermal management system parametric model for fuel cell powered aircraft conceptual design - Collares, Rodolfo da Silva (2024)
It is a widely accepted fact that the world ambient temperature is rising, and it is correlated with the CO2 emissions produced by economic sectors such as energy, industry and transports. Aerospace segment has an important contribution to the CO2 emissions, therefore it studies solutions to reduce or eliminate it from its products. The studies include the replacement of fossil fuel aeronautical engines per Fuel Cells, which are devices that operate with hydrogen and produce electrical energy, water, and heat. Since fuel cells release considerable amount of heat, it requires a substantial TMS (thermal management system), which impacts the airplane weight and drag. Studies of fuel cell powered aircraft have been published, and the TMS is not neglected, but a deep discussion regarding its weight and drag estimation was not found. The present work develops a TMS weight and drag parametric model for fuel cell powered aircraft conceptual design, based on fuel cell and radiators physical models, and representing an optimum compromise between weight and drag. The work reveals linear correlation between the TMS parameters and fuel cell power. Significant dependence on fuel cell temperature has also been shown, therefore, three temperature levels were tested. It has also been observed that optimum solutions tend to require too large radiators, difficult to install, so, a limitation was inserted in the optimization cycle and models for three different area limits were generated. Then, regression equations have been determined to correlate the TMS parameters with fuel cell power, for various combinations of fuel cell operating temperature and radiator area limits, accomplishing the purpose of the work. It is recommended, for future works, the conduction of studies to investigate more efficient radiators, heat enhancement devices and TMS large radiators installation solutions.